Arah Perkembangan Kajian Kepemimpinan Transformasional Kepala Sekolah dalam Pengembangan Inovasi Pembelajaran untuk Peningkatan Mutu Pendidikan - Muhammad Johan; Johar Permana; Diding Nurdin; Asep Suryana (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2020)
Abstract: This study aims to map the development of research on principal transformational leadership in promoting learning innovation for educational quality improvement. The study employed a Systematic Literature Review combined with bibliometric analysis. Data were retrieved from the Scopus database using the keywords “transformational leadership”, “educational innovation”, “quality of education”, and “principal” within the 2021–2026 publication period. A total of 32 documents were analyzed through document selection, metadata screening, descriptive analysis, and visualization using VOSviewer. The findings show that transformational leadership is the central keyword connecting teachers, principals, educational innovation, school leadership, and educational quality. The distribution of documents by author and affiliation indicates that this research area remains dispersed and is not yet dominated by particular authors or institutions. By country, Indonesia appears as the largest contributor, followed by Malaysia and China, suggesting strong scholarly attention to school leadership and educational innovation in the Asian context. This study concludes that principal transformational leadership plays a strategic role in promoting learning innovation through teacher motivation, creativity, collaboration, communication, and adaptive school culture. Future studies are recommended to expand data sources beyond Scopus, use a longer publication period, and develop deeper thematic analyses of the relationship between transformational leadership, learning innovation, and educational quality improvement. Keywords: transformational leadership; school principal; learning innovation; educational quality. Abstrak: Penelitian ini bertujuan untuk memetakan arah perkembangan kajian kepemimpinan transformasional kepala sekolah dalam pengembangan inovasi pembelajaran untuk peningkatan mutu pendidikan. Penelitian ini menggunakan metode Systematic Literature Review yang dikombinasikan dengan analisis bibliometrik. Data diperoleh dari database Scopus dengan kata kunci “transformational leadership”, “educational innovation”, “quality of education”, dan “principal” pada rentang tahun 2021–2026. Sebanyak 32 dokumen dianalisis melalui tahapan seleksi, pemeriksaan metadata, analisis deskriptif, dan visualisasi menggunakan VOSviewer. Hasil penelitian menunjukkan bahwa kata kunci transformational leadership menjadi simpul utama yang menghubungkan tema guru, kepala sekolah, inovasi pendidikan, kepemimpinan sekolah, dan mutu pendidikan. Distribusi dokumen berdasarkan penulis dan afiliasi menunjukkan bahwa kajian ini masih tersebar dan belum didominasi oleh penulis atau institusi tertentu. Berdasarkan negara, Indonesia menjadi kontributor terbesar, diikuti Malaysia dan China, yang menunjukkan kuatnya perhatian kawasan Asia terhadap isu kepemimpinan sekolah dan inovasi pendidikan. Penelitian ini menyimpulkan bahwa kepemimpinan transformasional kepala sekolah berperan strategis dalam mendorong inovasi pembelajaran melalui motivasi guru, kreativitas, kolaborasi, komunikasi, dan budaya sekolah adaptif. Penelitian selanjutnya disarankan memperluas sumber data selain Scopus, memperpanjang rentang waktu analisis, dan mengembangkan kajian tematik yang lebih mendalam mengenai hubungan kepemimpinan transformasional, inovasi pembelajaran, dan mutu pendidikan. Kata kunci: kepemimpinan transformasional; kepala sekolah; inovasi pembelajaran; mutu pendidikan.